Phenological and Electronic Information Aspects Of Introduction Research In The Mangyshlak Experimental Botanical Garden - I.F. BELOZEROV, A.A. IMANBAYEVA (International Journal of Advanced Science and Technology, 2020)
A description for a special computer program “Feno-S” created in Mangyshlak Experimntal Botanical Garden is given. The program is intended for entering and storing phytophenological information in the computer memory for its further rapid search, mathematical processing, identifying pheno-indicators of plant prospects, printing, plotting histograms and phenospectra, export in various text and graphic formats, compilation of reports and lists according to specified taxonomic, bioecological, decorative and phenological parameters. The characteristic of a simplified methodology for the collection, systematization and preparation for import into electronic databases of long-term phenological research material is given. Information is presented on the composition and structure of the currently formed database, which includes 130 information fields of symbolic, numerical, logical and temporary types and 4679 records by year for 534 taxa from 5 systematic divisions, 8 classes, 11 subclasses, 24 superorders, 49 orders, 8 suborders, 52 families and 108 genera.